2016
DOI: 10.7860/jcdr/2016/19097.8107
|View full text |Cite
|
Sign up to set email alerts
|

Study of Retinal Nerve Fibre Layer Thickness in Patients with Diabetes Mellitus Using Fourier Domain Optical Coherence Tomography

Abstract: This study positively concluded that neurodegeneration in an early component of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
5
23
2
Order By: Relevance
“…The thinning of the IMR also seemed to extend into the nasal OMR in TR and RNFL, which was particularly marked in RNFL. Our results are in line with those reported by others [ 3 , 4 , 13 , 16 , 17 , 18 , 19 ] in that the thickness of the inner retinal layers is reduced in patients with T2DM and this thinning is thought to be a marker of the beginning of neurodegenerative changes. While the majority of researchers evaluated the inner retinal layers, a number of studies [ 20 , 21 ] demonstrated morphological alterations in the choroidal and outer retinal layers in diabetes and DR.…”
Section: Discussionsupporting
confidence: 93%
“…The thinning of the IMR also seemed to extend into the nasal OMR in TR and RNFL, which was particularly marked in RNFL. Our results are in line with those reported by others [ 3 , 4 , 13 , 16 , 17 , 18 , 19 ] in that the thickness of the inner retinal layers is reduced in patients with T2DM and this thinning is thought to be a marker of the beginning of neurodegenerative changes. While the majority of researchers evaluated the inner retinal layers, a number of studies [ 20 , 21 ] demonstrated morphological alterations in the choroidal and outer retinal layers in diabetes and DR.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, no significant difference of RNFL thickness was found among the different DR severity groups. Previous studies [14,15] had similar results to ours, but some authors found significant RNFL thickness thinning in eyes with DR compared with the healthy controls [21,22]. e lack of significant difference in RNFL thickness in the peripapillary region among the groups observed herein could possibly be attributed to the structural changes in the retinal tissue in the peripapillary region caused by intracellular and extracellular edema, exudation, or glial fibrillary degeneration around the optic disc.…”
Section: Discussionsupporting
confidence: 83%
“…The exact relationship between DR and diabetic retinal neuropathy has not been fully explained yet. Some researchers have found that retinal neurodegeneration may occur in DM before any microcirculatory abnormalities become detectable [ 24 ]. They are also likely to occur in an independent manner [ 36 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Objective assessment of GCC finds importance in detection of inner retinal loss in patients with DM. Several studies reported GCC thinning in patients with DM without DR [ 23 , 24 ]. Our results are consistent with Srinivasan, who found an abnormality in GCC FLV in affected subjects and confirmed that the loss of neural tissue begins in the early stages of diabetes as an independent predictor of diabetic peripheral neuropathy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%